Effects of soluble guanylyl cyclase activation on skeletal muscle microcirculatory oxygen exchange in rats with heart failure with reduced ejection fraction - Weber, Ramona Elaine (Kansas State University, 2020)
Introduction: In heart failure (HF), nitric oxide (NO) pathway dysfunction impairs muscle arteriolar vasodilation and thus capillary hemodynamics, contributing to impaired oxygen uptake (V̇O₂) kinetics. Due to poor prognosis and enhanced muscle fatigability following myocardial infarction, new treatment options are pursued heavily. To target downstream effects of NO directly, soluble guanyl cyclase (sGC) activators were developed. This investigation tested the hypotheses that chronic administration of a sGC activator would increase the O₂ delivery (Q̇O₂)-to-O₂ utilization (V̇O₂) ratio in the skeletal muscle interstitial space (PO₂is) of HF rats during twitch contractions due, in part, to increases in red blood cell (RBC) flux (f[subscript]RBC) and hematocrit (Hct[subscript]cap). Furthermore, we investigated whether exogenous NO (sodium nitroprusside, SNP) superfusion in addition to sGC activator would improve the Q̇O₂-V̇O₂ ratio and capillary hemodynamics further. Methods: HF was induced in adult male Sprague-Dawley (3-4 mo. old) rats via myocardial infarction (MI). Following ~3 weeks of HF progression, 0.3 mg/kg sGC activator in 1 ml vehicle (10% Transcutol, 20% Cremophor, Sigma Aldrich, St. Louis, MO, and 70% water) was administered via oral gavage twice a day (HF + sGC; n =10) for 5 days prior to phosphorescence quenching (PO₂is, in contracting muscle) and intravital microscopy (rest) measurements in the spinotrapezius muscle. The control heart failure group (HF; n = 9) received vehicle only. Intravital microscopy measured f[subscript]RBC, V[subscript]RBC, and Hct[subscript]cap under resting conditions. Results: Intravital microscopy revealed greater increases in Hct[subscript]cap (+16 ± 1 vs 10 ± 1%) of HF + sGC vs HF, respectively. Interestingly, f[subscript]RBC and V[subscript]RBC respectively, were both increased in HF + sGC vs HF (70 ± 9 vs 25 ± 8 RBC/s) and (490 ± 43 vs 226 ± 35 μm/s) (P < 0.05). A greater number of capillaries supporting flow was seen in HF + sGC (91 ± 3 vs 82 ± 3%, P < 0.10). f[subscript]RBC and V[subscript]RBC were strongly correlated (r = 0.958). During 14-22 seconds of contractions there was an increase in PO₂is in HF + sGC vs HF (P ≤ 0.05). Conclusions: Our findings suggest that increased resting Q̇O₂ via f[subscript]RBC, V[subscript]RBC, and Hct[subscript]cap allow for better Q̇O₂-to-V̇O₂ matching, reversing a likely limitation to HF, while also avoiding pernicious interactions with reactive oxygen species or tolerances experienced with NO supplementation. Additionally, during the rest-contraction transient, sGC activator increases PO₂is, which may speed V̇O₂ kinetics. Together, our findings support that sGC activators as a potential therapeutic targeting vasomotor dysfunction in HF which would be expected to increase exercise capacity by speeding V̇O₂ kinetics.
Keywords: heart failure; skeletal muscle; oxygen transport; microcirculation; soluble guanylyl cyclase; exercise